HUBUNGAN KECERDASAN EMOSIONAL DAN LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN - Irsyad Ali Amin; Muhammad Nur Rianto Al Arif; Rahmah Putri Wijayanti (JURNAL LENTERA BISNIS, 2024)
This study aims to analyze emotional intelligence and financial literacy on financial behavior in economics and business students at Prof. Dr. HAMKA Muhammadiyah University. The data in this study are primary data obtained from the results of distributing questionnaires to economics and business students at Uhamka. The analysis method used to test the hypothesis is multiple linear regression analysis with the Ordinary Least Square (OLS) method. The results of this study indicate that of the two independent variables, has a significant influence on financial behavior both simultaneously and partially. Key words: Emotional Intelligence, Financial Literacy, Financial Behavior